Epistemic responsibility in the face of a pandemic - Levy, N; Savulescu, J (Oxford University Press, 2020)
The COVID-19 pandemic currently wracking the world represents a crucial test for our ethical toolkit. Governments, institutions and individuals are suddenly called upon to make life and death decisions for which they typically ill-prepared. Vocabulary which has suddenly become so familiar—“flatten the curve”; “social distancing”; “R0”—was unknown to most of us a bare few weeks ago. Even for experts, every option continues to have huge uncertainties associated with it. When experts are divided and unsure, how are the rest of us responsibly to decide how to act and who to trust?